Modulation of interleukin 2 receptor expression on normal human lymphocytes by thymic hormones. - Sztein, M B (1986)
The expression of interleukin 2 receptors (IL-2R) is a critical step leading to normal lymphocyte proliferation. Since thymosin fraction 5 (TF5), a thymic hormone preparation, enhances lymphoproliferative responses of human cells, we examined the effects of TF5 on the expression of IL-2R on mitogen-stimulated human lymphocytes. TF5 significantly increased the percentage and antigen density of cells expressing IL-2R after stimulation with an optimal concentration of phytohemagglutinin (PHA) when the cells from the same donor exhibited suboptimal responses to PHA alone. The same effect was observed with a suboptimal PHA concentration and with OKT3 monoclonal antibody stimulation. Thymosin alpha 1, a synthetic polypeptide originally isolated in its native form from TF5, was also able to increase IL-2R expression in response to PHA, suggesting that it is the active species in TF5. The enhancement of IL-2R expression was paralleled by increased proliferative responses. Increased IL-2R expression appears to be the direct effect of thymic hormones, since abrogation of interleukin 2 production by cyclosporin A did not affect TF5-mediated enhancement of PHA-induced IL-2R expression. These results point to a physiological role of thymic hormones in the maintenance of normal levels of IL-2R expression. This immunoregulatory activity of thymic hormones might be relevant in the treatment of conditions where there is decreased IL-2R expression, such as the acquired immune-deficiency syndrome, or in the restoration of normal IL-2R expression to lymphocytes from aged individuals.